2010
DOI: 10.1105/tpc.110.075986
|View full text |Cite
|
Sign up to set email alerts
|

Crossovers Get a Boost inBrassicaAllotriploid and Allotetraploid Hybrids

Abstract: Meiotic crossovers are necessary to generate balanced gametes and to increase genetic diversity. Even if crossover number is usually constrained, recent results suggest that manipulating karyotype composition could be a new way to increase crossover frequency in plants. In this study, we explored this hypothesis by analyzing the extent of crossover variation in a set of related diploid AA, allotriploid AAC, and allotetraploid AACC Brassica hybrids. We first used cytogenetic methods to describe the meiotic beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 53 publications
11
77
5
Order By: Relevance
“…In the present study, AA.CC and CC.AA presented relatively high rates of univalents and the highest rate of homeologous pairing, as in other synthetic B. napus observed with the same BAC clone BoB014O06 from B. oleracea (Leflon et al 2010). But AA.CC had high pollen fertility while CC.AA had much lower fertility, which was possibly caused by the cytoplasmic effects.…”
Section: Genome Relatedness and Chromosome Behavior In Synthetic Allosupporting
confidence: 60%
See 1 more Smart Citation
“…In the present study, AA.CC and CC.AA presented relatively high rates of univalents and the highest rate of homeologous pairing, as in other synthetic B. napus observed with the same BAC clone BoB014O06 from B. oleracea (Leflon et al 2010). But AA.CC had high pollen fertility while CC.AA had much lower fertility, which was possibly caused by the cytoplasmic effects.…”
Section: Genome Relatedness and Chromosome Behavior In Synthetic Allosupporting
confidence: 60%
“…The hybrids with Darmor-bzh of high pairing presented a reduction of autosyndesis within C genome, particularly of A-C allosyndesis compared with its haploid (Nicolas et al 2007), showing that PrBn on the C genome failed to enhance or affect the pairing of its own chromosome in the AAC background. However, cytogenetic estimation of class I crossovers (interfering crossovers) in the entire genome by immunolocalization of a key protein, MutL Homolog1, showed that crossover rates were significantly higher in the allotetraploid AACC hybrid than in the diploid AA hybrid and were highest in the allotriploid AAC hybrid (Leflon et al 2010).…”
Section: Genome Structure Of Brassica Diploidsmentioning
confidence: 99%
“…When plants carrying one extra C 9 chromosome (AA + 1C 9 ) were examined, the recombination rate was 2.7-fold higher than that of the AA diploid genome. This finding suggests that the number of unpaired C chromosomes and the presence of specific C chromosomes in the hybrids modulated the frequency of COs on the AA genome (Leflon et al, 2010;Suay et al, 2014).…”
Section: Meiosis In Allopolyploid Speciesmentioning
confidence: 77%
“…The increase of CO formation in the AAC triploid hybrid was accompanied by an increase in the number of MLH1 foci at diakinesis, implying that, at least in part, this was due to an elevation of class I interference-sensitive COs. The study also revealed that the allotetraploid (AACC) displayed an increase in COs to a level intermediate between the diploid (AA) and allotriploid (AAC) hybrid (Leflon et al, 2010). Even more remarkably, in a subsequent study, the same workers examined hybrids containing the diploid A genome combined with different numbers or specific individual C chromosomes.…”
Section: Meiosis In Allopolyploid Speciesmentioning
confidence: 94%
“…Comparative genetic mapping between polyploid species and their diploid relatives allows a better understanding of the evolution of genome structure and associated rearrangements. Linkage analyses have uncovered further genomic consequences of polyploidization, including increased rates of recombination in polyploid plants relative to diploid ancestors (e.g., Leflon et al, 2010;Pecinka et al, 2011;reviewed in Grandont et al, 2013) as well as homeologous (i.e., intergenomic) recombination, shown to occur in polyploid plants (Gaeta et al, 2007) and salamanders Bogart, 2006, 2010). Thus, provided one may identify the parental species and timing of hybridization events, allopolyploid lineages represent unique opportunities to address important questions regarding the reorganization of genomes that is expected to follow hybridization, and more generally to gain crucial insights on the evolutionary dynamics of genomes.…”
Section: Introductionmentioning
confidence: 99%